Use of peptide-major histocompatibility complex tetramer technology to study interactions between Staphylococcus aureus proteins and human cells. - Massey, R; Scriba, T; Brown, E; Phillips, R; Sewell, A (2007)
In this study, we report the use of peptide-major histocompatibility complex tetramer technology to study the interactions that occur between Staphylococcus aureus proteins and human leukocytes. We demonstrated that this technology can be used to study the activity of superantigens such as toxic shock syndrome toxin 1 and also found that despite similarities to known proteins (i.e., major histocompatibility complex [MHC] class II molecules and superantigens), the S. aureus Eap protein does not block MHC-T-cell receptor interactions and is not a superantigen. Instead, it has nonspecific cross-linking activity that is dependent upon having at least two of its six 110-amino-acid repeats.